Simon Watteyne, Lever l’impôt en Belgique. Une histoire de combats politiques (1830–1962). Brüssel, CRISP 2023 - Huybrechts, Yves (Historische Zeitschrift)

The impact of market power on banks' ESG scores - evidence from Europe and North America - Voigt, Simone; Uhde, André
This paper empirically examines the relationship between market power and Environmental, Social, and Governance (ESG) scores of banks in Europe and North America from 2010 to 2021, focusing separately on loan and deposit markets. Employing the Lerner Index as a non-structural measure of market power, our findings suggest that the impact of banking market power on ESG scores varies by region and the respective loan or deposit market. We find a negative effect of loan and deposit market power on ESG scores of European banks whereas the opposite effect can be observed for North American banks exhibiting loan market power. Further sensitivity analyses reveal that factors such as banks being Global Systemically Important (G-SIBs), and different ESG-related events like the Paris Agreement, the reemergence of the #MeToo movement and the COVID-19 pandemic may also explain the relationship between bank market power and ESG scores. Overall, our results underline that banking market power plays a pivotal role in enforcing ESG commitments in banking, offering key insights for policymakers, regulators, and banking stakeholders.
Keywords: Market Power; ESG scores; European and North American banking markets

Impulse zur Stochastik in der Oberstufe - Biehler, Rolf; Binder, Karin; Haverkamp, Michael; Kempen, Leander (Mathematikabitur „Status Quo – Quo Vadis“: Tagungsband zur Fachtagung zum Mathematikabitur am 11./12. Februar 2025 in Dresden)

The nexus of market power and female board representation in European banks - Voigt, Simone
This paper empirically investigates the relationship between market power and female board representation in large commercial banks in the EU-27 from 2020 to 2024. Using the Lerner Index as a proxy for market power and hand-collected data on female board representation, the findings suggest that increasing market power is detrimental to a bank’s likelihood of reaching the 33 percent gender diversity target for the board of directors, as proposed by the EU Directive EU2022/2381. The negative effect is especially pronounced for listed banks and systemically important banks, highlighting the importance of considering banking market structures (market power and competition) when enforcing regulatory diversity standards for those banks in particular.

Parental (dis)satisfaction with school placement to achieve inclusion: a cross-country comparison - Johansson, Veslemøy Maria Fossum; Gibson, Suanne; Woodcock, Stuart; Dechsling, Anders; Kullmann, Harry; Herrebrøden, Marte Karoline; Ulriksen, Line-Britt; Nordahl-Hansen, Anders (Frontiers in Education)
Background This study draws on data from a larger international project exploring parents' perceptions of the education of their children with special educational needs and/or disabilities (SEND). Using responses from 1,309 parents in Australia, England, Germany, and Norway it examines parental satisfaction with mainstream and special schools, and parents' school placement preferences, including willingness to change schools. Parental satisfaction is assessed as an overall evaluation of how well the child's school placement meets their needs, without distinguishing between specific aspects of the school experience. The study also explores whether the child's level of support is associated with these perceptions. Based on a human rights perspective, we highlight parents’ perspectives and their role in the development of more inclusive education systems, without promoting one model of schooling over another. Methods Responses from 1,309 parents across four countries were analysed using descriptive and inferential statistics. Non-parametric tests compared satisfaction across school types, chi-squared tests assessed associations with willingness to change schools, and binary logistic regression examined whether level of support was associated with parents' willingness to change school placement. Results Parents in England, Germany, and Norway reported higher satisfaction with special schools than with mainstream schools. No statistically significant difference was observed in Australia. Parents of children in special schools were less likely to report considering changing schools, particularly in England and Norway. Higher pupil support needs were significantly associated with parents’ willingness to change school across the combined sample. These findings suggest that parental satisfaction with their child's education and their preferences regarding school placement may be shaped by both school type and how well pupils' support needs are perceived to be met. Discussion and conclusion The role of parents as key stakeholders in developing inclusive education systems, consistent with the Convention on the Rights of Persons with Disabilities (CRPD) is emphasised. While parents in special schools in three of the four countries reported higher satisfaction, the reasons for this remain unclear. Understanding the factors shaping parental satisfaction is essential for developing inclusive and responsive learning environments. These findings offer a starting point for future research on how education systems can better align policy commitments with families’ lived experiences.

The catalyst that stores charge first - Linnemann, Julia; Leppin, Christian (Bunsen-Magazin)
Alkaline oxygen evolution on Co3O4 involves more than adsorption and electron transfer at a fixed surface. The article draws on operando electrochemical quartz crystal microbalance with dissipation monitoring (EQCM-D), surface X-ray diffraction (SXRD), Raman, UV/Vis and impedance spectroscopy. On this basis, it discusses pseudocapacitive oxidation of cobalt ion sites, electrolyte uptake and near-surface transformation, and asks which of these changes are kinetically coupled to electrocatalysis.
Keywords: electrocatalysis; oxygen evolution reaction; cobalt spinel; operando characterization; spectroelectrochemistry

Review: Florian Wobser/ Philipp Thomas (Hrsg.): Philosophische Bildung neu Denken. Perspektiven auf die Vielfalt der Vernunft. Bielefeld: transcript 2025. 284 S. - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

Philosophieren in der Krise ist keine Krise des Philosophierens! - Albus, Vanessa (Mitteilungen des Fachverbandes Philosophie)

Den eigenen Rucksack kennen - Intrapersonale Fähigkeiten von Lehrkräften als Schlüssel für aktivierende Hochschullehre - Lüttke, Jan-Phillip; Beutner, Marc; Happ, Saskia (Voneinander Lehren lernen)
Die Verschiebung des ersten Kontakts mit Lerninhalten in selbstgesteuertes Lernen, vor einer vertiefenden, kooperativen Präsenzphase, im Rahmen des Inverted Classroom Model (ICM), verändert die professionelle Rolle der Lehrenden: Sie moderieren, statt zu dozieren, und müssen Unvorhergesehenes handhaben. Darin liegt gleichzeitig die Chance des ICM, da sich Potenziale und Herausforderungen zeigen, die den Reflexionsprozess fördern können. Vor diesem Hintergrund untersucht der Beitrag, wie das ICM die Entwicklung intrapersonaler Kompetenzen unterstützen kann. Zentrale intrapersonalen Kompetenzen sind Emotionsregulation, Resilienz, Selbstwirksamkeit und Reflexivität. Während Lehrende in der Pre-Class-Phase des ICM potenzielle Belastungen antizipieren können, findet in der In-Class-Phase eine Echtzeit-Reflexion im Unterrichtshandeln statt. Erkenntnisse aus der Post-Class-Phase werden in die zukünftige Lehrplanung überführt. Die vorgeschlagene Reflexionsarchitektur verknüpft Wahrnehmen, Deuten, Regulieren, Transferieren mit den ICM-Phasen. Der “Rucksack” dient dabei als Strukturhilfe für die Reflexion des eigenen „professionellen Gepäcks“. Für die Praxis wird eine Kombination aus Fallanalysen, Leitfragen und kollegialem Austausch vorgeschlagen.

Geld regiert die Welt: Inklusion als Budgetverliererin (bildungs-) politischer Sparmaßnahmen - Happ, Saskia

Übernahme statt Übergabe: Eine literaturbasierte Begründung für mehr Verantwortung für Inklusion an Hochschulen - Happ, Saskia; Lüttke, Jan-Phillip; Beutner, Marc

Qualifikationsanforderung: Inklusion - Passungsprobleme zwischen Kompetenzen und Anforderungsprofil - Happ, Saskia (k:ON - Kölner Online Journal für Lehrer*innenbildung)
Vor dem Hintergrund zunehmender inklusiver Anforderungen an Lehrkräfte wird untersucht, inwieweit bestehende Rahmenwerke der Lehramtsstudiengänge ebendiesen inklusiven Anforderungen noch gerecht werden. Dazu werden ausgewählte Prüfungsordnungen hinsichtlich ihrer inklusionsbezogenen Inhalte analysiert und mit dem Anforderungsprofil von Lehrkräften verglichen. Ziel ist es, mögliche Diskrepanzen zwischen akademischer Qualifikation und inklusiver Arbeitsrealität herauszustellen.
Keywords: Lehrer*innenbildung; Inklusion; Professionalisierung

Steuern, Standort, Unternehmensstrategie – Wie wettbewerbsfähig sind Deutschlands Steuer-, Zoll- und Investitionspolitik? - Kaeser, Christian; Schanz, Deborah; Sureth-Sloane, Caren (Schmalenbach IMPULSE)

Redesigning the TETRISC Architecture for Scalable Rocket Chip Implementations - Hannemann, Kai Arne; Luchterhandt, Lars; Müller, Wolfgang; Ulbricht, Markus; Lu, Li (38. ITG / GMM / GI - Workshop Testmethoden und Zuverlässigkeit von Schaltungen und Systemen)
Resilient systems require monitoring and prediction of environmental and intrinsic conditions and the ability to adapt to changing circumstances to optimize the trade-off between performance, power consumption, and fault tolerance. TETRISC was introduced as a resilient multicore RISC-V processor system based on the PULPissimo platform. This paper presents the migration of TETRISC to the Rocket Chip SoC, which is freely scalable to the number of processors through parametrizable Chisel models. As such, we discuss and evaluate the main advantages and obstacles that come with the Chipyard framework for RTL simulation and FPGA synthesis for the rapid prototyping of resilient, scalable architectures that are online configurable through software for different multicore and lock-step modes.
Keywords: RISC-V; Multicore; Fault Tolerant; TETRISC; Chisel; Chipyard

TETRISC on Rocket Chip: A Scalable and Adaptive RISC-V Multicore Architecture - Hannemann, Kai Arne; Luchterhandt, Lars; Müller, Wolfgang; Ulbricht, Markus; Lu, Li; Scheytt, J. Christoph (29. Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV 2026))
Resilient systems require monitoring and prediction of environmental and intrinsic conditions, as well as the ability to adapt to environmental hazards while optimizing the trade-off among performance, power consumption, and fault tolerance. TETRISC was introduced as a resilient multicore RISC-V processor system based on the PULPissimo platform. We introduce the migration of TETRISC to the open-source Rocket Chip SoC, targeting scalable TETRISC Chisel implementations. As such, we discuss and evaluate the main advantages and obstacles that come with the Chipyard framework for RTL simulation and FPGA synthesis, enabling rapid prototyping of resilient, scalable architectures configurable for multicore and lockstep modes.

Aqueous Lubrication in Geared Transmissions: A Review on Mechanisms, Superlubricity, Efficiency Potential, and Remaining Barriers - Hofmann, Stefan; Lohner, Thomas; Stahl, Karsten; Schwarze, Hubert; Koch, Oliver; Zander, Daniela; Stebl, Michael; Schümann, Ulrike; Marian, Max; Magyar, Balázs; Jacobs, Georg; König, Florian; et al. (Tribology Transactions)

Benchmarking semiempirical quantum chemical methods on liquid water - Wu, Xin; Elgabarty, Hossam; Alizadeh, Vahideh; Henao, Andrés; Zysk, Frederik; Plessl, Christian; Ehlert, Sebastian; Hutter, Jürg; Kühne, Thomas D. (The Journal of Chemical Physics)
Stimulated by the renewed interest and recent developments in semiempirical quantum chemical (SQC) methods for noncovalent interactions, we examine the properties of liquid water under ambient conditions by means of molecular dynamics (MD) simulations, both with the conventional neglect of diatomic differential overlap-type methods, e.g., AM1 and PM6, and with DFTB-type (density-functional tight-binding) methods, e.g., DFTB2 and GFN-xTB (Geometry-Frequency-Noncovalent eXtended Tight-Binding). Besides the original parameter sets, some specifically reparameterized SQC methods (denoted as AM1-W, PM6-fm, and DFTB2-iBi) targeting various smaller water systems ranging from molecular clusters to bulk are considered as well. The quality of these different SQC methods for describing liquid water properties under ambient conditions is assessed by comparison with well-established experimental data and also with BLYP-D3 density functional theory-based ab initio MD simulations. Our analyses reveal that static and dynamic properties of bulk water are poorly described by all considered SQC methods with the original parameters, regardless of the underlying theoretical models, with most of the methods suffering from too weak hydrogen bonds and hence predicting a far too fluid water with highly distorted hydrogen bond kinetics. Meanwhile, the reparameterized force-matched PM6-fm method is shown to be able to quantitatively reproduce the static and dynamic features of liquid water and thus can be used as a computationally efficient alternative to electronic structure-based MD simulations for liquid water that requires extended length and time scales. DFTB2-iBi predicts a slightly overstructured water with reduced fluidity, whereas AM1-W gives an amorphous ice-like structure for water under ambient conditions.

Intelligent headlights boost energy efficiency and drive decarbonization - Fittkau, Niklas; Bußemas, Leon; Malena, Kevin; Gausemeier, Sandra; Trächtler, Ansgar (2026 IEEE Intelligent Vehicles Symposium (IV))
The key to achieving energy efficiency and reducing carbon emissions in transportation lies in the effectiveness of vehicles and their associated mechatronic systems. A notable example of a mechatronic system is the headlamp at the front of a vehicle, which emits adaptive headlights, such as the well-known adaptive cornering lights or glare-free high beam. The rise of these and other Advanced Driver Assistance Systems (ADAS) has led to a proliferation of sensor data. However, the full potential of ADAS sensor data for increasing energy efficiency has not yet been exploited in the past. This study demonstrates that utilizing the data to dynamically adapt headlights to the upcoming driving scenario leads to a substantial reduction in power consumption. This objective is pursued by focusing on the predominant carbon footprint driver, namely the low beam.
Keywords: intelligent headlights; energy efficiency; ecodriving; decarbonization; matrix LED headlights; adaptive realtime control; ADAS systems; feedforward control; simulation

Understanding the Value of Data Ecosystems for Circular Economy Metrics - Pottebaum, Jens; Dietrich, Katrin; Schmidt, Lara; Biglari, Mostafa; Schmidt, Michael-Georg; Pistillo, Alessandro; Gravina, Nadja; Schmidt, Franziska
The Circular Economy is considered a key approach to addressing resource scarcity, rising raw material prices, and the need for more resilient value chains. However, its practical implementation is often hindered by the lack of suitable and standardized metrics, as well as by high requirements for horizontal and vertical data integration. This white paper illustrates, through selected Manufacturing-X projects, how federated data ecosystems can help establish Circular Economy metrics as an effective management instrument for growth, margin protection, and resilience. Based on literature, industrial practice, and demonstrators, Circular Economy metrics are structured into four groups: overarching assessment approaches, disassembly-related indicators, lifetime-oriented metrics, and end-of-life and recycling-focused indicators. Use cases from Construct-X, Decide4ECO, Fluid 4.0, Chem-X, and other Manufacturing-X initiatives demonstrate the benefits of data-driven approaches for product, component, and material loops. At the same time, they reveal a current lack of interoperable, cross-industry standards for both metrics and data models. The white paper concludes that data ecosystems such as Manufacturing-X are a key enabler for scaling circular business models. In particular, shared cross-sector frameworks for metrics, standardized information models based for example on the Asset Administration Shell, and the integration of circular metrics into existing systems and processes are essential. The work presented therefore marks an important step toward a data-driven and economically viable Circular Economy.
Keywords: Circular Economy; Circular Economy Metrics; Manufacturing-X; Data Ecosystems

Method for estimation of plate heat exchanger design for a flexible methanol–water distillation column - Arsenyeva, Olga; Breuer, Niklas; Riepin, Yevhenii; Grünewald, Marcus; Riese, Julia (Thermal Science and Engineering Progress)